2015
DOI: 10.3109/03014460.2015.1044469
|View full text |Cite
|
Sign up to set email alerts
|

The Danish approach to forensic age estimation in the living: how, how many and what’s new? A review of cases performed in 2012

Abstract: The current procedure is not mathematically or statistically satisfactory. Instead, the most likely age including the variation and error of the age estimate should be reported in statements. The introduction of a Bayesian approach and the use of post-mortem-imaging-based databases may be used for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…Although previous research has already revealed many aspects of skeletal and dental development, authors keep stressing the importance of further investigation to enable scientists and authorities to optimise and standardise age estimation practices (Buckberry, 2015, Larsen et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has already revealed many aspects of skeletal and dental development, authors keep stressing the importance of further investigation to enable scientists and authorities to optimise and standardise age estimation practices (Buckberry, 2015, Larsen et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…2020 Aldursgreiningar fylgdarlausra barna svarar til u.þ.b. +/-2 staðalfrávika (58). Kölkun í miðlaegu brjóski viðbeins er haegt að skoða með venjulegri röntgenmynd eða með sneiðmynd (Ct) (63,64) og lokastig naest þegar einstaklingur er eldri en tvítugur.…”
Section: Svíþjóðunclassified
“…Sá samningur var ekki endurnýjaður á grundvelli þess að ekki hafi verið staðið við ákvaeði samnings að mati háskólaráðs, að ekki hafi verið leitað allra leiða áður en kaemi til aldurs greining af tönnum m.a kröfu um sálfraeðiviðtöl, enda þótt fyrir liggi að þau þjóni engu vísindalegu gildi og engin rannsóknargögn styðja beitingu, gagnsemi eða áreiðanleika sálfraeðilegra aldursgreiningar (AgFAd) (40), nema að ekki er að öllu jöfnu tekin röntgenmynd af viðbeini, til að spara notkun röntgengeisla og ekki er framkvaemd klínísk tanna-og munnholsskoðun. AgFAd maelir með eftirfarandi aðferðafraeði: 1. líkamlegri skoðun 2. greining beinþroska með töku röntgenmyndar á á vinstri hönd og úlnlið og ef þarf rannsókn á viðbeini og 3. tannþroska með röntgenrannsókn á tönnum og kjálkum (58). Í flestum löndum markar 18 ára aldur mun á barni og fullorðnum.…”
Section: íSlandunclassified
See 2 more Smart Citations